A complex odontoma of the anterior maxilla associated with an erupting canine. (12th November 2013) - Pillai, Ajay; Moghe, Swapnil; Gupta, Mithilesh K; Pathak, Abhishek
Abstract : Many developmental anomalies of the jaw are accidentally diagnosed during radiographic investigations for other symptoms. Complex odontomas are odontogenic tumours, relatively rare in the anterior maxilla and generally asymptomatic. Frequently the odontoma may interfere with the eruption of teeth. This paper describes a case of complex odontoma in an 8-year-old girl, which resulted in the palatal displacement of the lateral incisor and an erupting permanent canine. A calcified mass was seen on the radiograph and was provisionally diagnosed as an odontoma which was surgically enucleated. Routine follow-up was carried out for more than 1 year and no recurrence was seen.